Father Brown. Season five [videorecording (DVD)] - Williams, Mark, 1959-; Deam, Jack, 1972-; Cusack, Sorcha, 1949- (BBC, 2017)
Father Brown cycles back for another season of more mysteries in the sleepy Cotswold village of Kembleford. This season, a Duke and Duchess visit the village at Christmas time, but the community is thrown into chaos when the couple's baby boy goes missing. When a female author is murdered, Father Brown turns to her novels for guidance. And when a boxer is found dead in suspicious circumstances, Father Brown uncovers a well-planned betting sting.